Enhanced Solubility and Permeability of Salicis cortex Extract by Formulating as a Microemulsion - Piazzini, Vieri; Bigagli, Elisabetta; Luceri, Cristina; Bilia, Anna Rita; Bergonzi, Maria Camilla (Planta Medica, 2018)
A microemulsion system was developed and investigated as a novel oral formulation to increase the solubility and absorption of Salicis cortex extract. This extract possesses many pharmacological activities, in particular, it is beneficial for back pain and osteoarthritic and rheumatic complaints. In this work, after qualitative and quantitative characterization of the extract and the validation of an HPLC/diode array detector analytical method, solubility studies were performed to choose the best components for microemulsion formulation. The optimized microemulsion consisted of 2.5 g of triacetin, as the oil phase, 2.5 g of Tween 20 as the surfactant, 2.5 g of labrasol as the cosurfactant, and 5 g of water. The microemulsion was visually checked, characterized by light scattering techniques and morphological observations. The developed formulation appeared transparent, the droplet size was around 40 nm, and the ζ-potential result was negative. The maximum loading content of Salicis cortex extract resulted in 40 mg/mL. Furthermore, storage stability studies and an in vitro digestion assay were performed. The advantages offered by microemulsion were evaluated in vitro using artificial membranes and cells, i.e., parallel artificial membrane permeability assay and a Caco-2 model. Both studies proved that the microemulsion was successful in enhancing the permeation of extract compounds, so it could be useful to ameliorate the bioefficacy of Salicis cortex.
Keywords: icroemulsion; Salix species; Salicaceae; oral delivery; PAMPA; Caco-2 cells